Motivation of Running Community Members in Semarang City - Wahyu Fitri Adi; Adiska Rani Ditya Candra (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. This study aims to determine the level of motivation among running community members in Semarang City regarding the sport of running.